Peningkatan Minat dan Motivasi Santri Pesantren Al-‘Ashry dalam Pembelajaran Matematika dengan Teka-Teki Matematika Persegi Ajaib - Hazmira Yozza; Izzati Rahmi HG; Budi Rudianto; Admi Nazra; Noverina Alfiany; Deswelyyanti Deswelyyanti; Ferra Yanuar; Dodi Devianto (Warta Pengabdian Andalas, 2023)
Mathematics is one of the most essential basic sciences because it closely relates to everyday life and the development of other disciplines. It should be taught at every education level, likewise for Islamic boarding school students. In addition to having extensive religious knowledge, students must also have increased thinking, logic and reasoning. In addition, mathematics is also an essential tool in studying several topics of Islamic law, such as inheritance law and zakat. Therefore, mathematics must be taught in the education and teaching curriculum at the Islamic boarding school, including the As-'Ashry Islamic Boarding School. One of the obstacles the Al-'Ashry Islamic boarding school faces in teaching mathematics is that students need more interest and motivation in learning mathematics. Therefore, this community service activity was carried out to increase the interest and motivation of students to learn mathematics. The activity was held on December 7, 2022. The activity was carried out in two forms: a motivational lecture and a math puzzle called Magic Square. Based on the evaluation carried out by the community service team, it was evident that the students were interested in the activities carried out. Students were fully involved in every activity carried out.